Evaluating the contribution of the Algerian pharmaceutical industries to the balance of the national pharmaceutical market - Aggoun, Charaf; Bouruina, Aziz; Boukhedouni, Loukman (Finance and Business Economies Review, 2019)
The aim of this paper to highlight the Algerian pharmaceutical industry. And how far it has contributed to improve Algerian pharmaceutical market indices; by covering market needs and reduce Drug imports and export support. It had also tried to present developments of the pharmaceutical industry sector in Algeria. and evaluate the strengths and weaknesses in this sector. The conclusion of the study was that; despite Algerian pharmaceutical industry contributions to Satisfaction of market needs, but that is not enough because the growth of the Algerian pharmaceutical market is caused by growing imports. And that the contribution of the local product in export has not yet reached the required level. On the other hand, The Algerian pharmaceutical industries have not been able to take advantage of local and external market opportunities.